Maya Angelou, the Angel of Protest: A study of her select poems - Nagamani, K. (International Journal of Psychosocial Rehabilitation, 2020)
The present paper entitled, “Maya Angelou, the Angel of Protest: A Study of her select poems” tries to reiterate how Angelou had been a strong yet positive voice of the oppression experienced by the Blacks and in addition as the „other‟. Maya Angelou‟s poetry addresses the issues of social and political subjugation and the dominance of patriarchy dormant for centuries. The poems are the so far unspoken voices of the multitude, celebrating the sense of self-respect and beauty, specifically of the black woman and women in general. The poem„Phenomenal Woman‟ is a canto of praise that of the inherent beauty in a woman, whereas „Still I Rise‟ is the cry for liberation and an assertion of indomitable spirit of womanhood never to be bowed down by life‟s odds and human‟s follies. „I know why the Caged Bird Sings‟ is an anthem of hope and optimism even in the midst of desperate confinement and oppression. Her poems resonate with positivity and hope and a liberating power.